Pregravidary preparation - Yu. S. Podilyakina; D. V. Kulov; Zh. T. Amirbekova (Исследования и практика в медицине, 2021)
Preconception care is an essential component of promoting maternal and child health at the national and international levels. The term “preconception care” is found both in various recommendations of the World Health Organization and in practical recommendations for the protection of maternal and child health. Although programs and guidelines may differ depending on local needs (endemic diseases, financial security, educational level of the population, etc.), the general concept of preconception care is present in developing and developed countries within different health systems and does not depend on political, cultural or religious beliefs. In addition, the history of incorporating various preconception strategies and ideologies into international maternal and child health programs and policies spans nearly 30 years, demonstrating the long-term recognition of the relative importance of this approach as a means of optimizing pregnancy outcomes. However, at present there is a large proportion of women who do not know about the importance of preparing for pregnancy.The purpose of this review was to study international experience in the implementation of preconception care in the practice of practical health care professionals. The main tools were highlighted – motivated counseling and reflective practice. Since the United States of America is the world health leader in improving pregnancy outcomes, the information sources were selected from PubMed and the Centers for Disease Control. This review provides evidence of the importance of motivated counseling, identifies the main stages of establishing a trusting relationship between a doctor and a woman or a married couple.Conclusions. Correct pregravid behavior will improve the demographic indicators of the country, however, systematic work is needed with regard to the social responsibility of married couples and the interest of medical personnel in high-quality motivated counseling.